Analisa Kebutuhan Bahasa Inggris untuk Meningkatkan Keterampilan Berbahasa Inggris bagi Pelaku UMKM di Kampung Bandar Kota Pekanbaru - Aulia Agustiani; Maryantina Maryantina; Sefrona Syaiful (Departement of Mathematics Education, 2023)
Research was conducted out in August-October 2022, with the title: Need Analysis of English to Improve English Skills of Micro Smll Medium Enterprises at Kampung Bandar- Pekanbaru City. This study aimed to find out thet need of English to improve English skills of micro small and medium enterprises at Kampung Bandar- Pekanbaru City. This study used a qualitative descriptive method to obtain primary and secondary data where data collection was done by distributed questionnaires and interviews. The results obtained from this study revealed that the micro small and medium enterprises at Kampung Bandar-Pekanbaru City, still really need the English language to support their work. From the self-assessment/self-evaluation, it is known that the majority of local guides learn English from school. In terms of English proficiency, the local guide states that basic are 60% of respondents. Furthermore, there are several points that Micro Small and Medium Enterprises must master in welcoming foreign tourists, especially in the fields of greeting, welcoming the tourist, and saying goodbye.